Tax Fairness in Women Taxpayers' Non Taxable Income (PTKP) and Women's Labor Force Participation Rates - Wijayanto, Danang; Rahayu, Andini Dwi; Arieftiara, Dianwicaksih (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research aims to analyze the fairness of tax rules for women taxpayers and their relationship to the women work participation rate. This is motivated because in Indonesia there is an imbalance in non-taxable income (PTKP) regulations for women and men employees, especially in the formal sector, which in turn has an impact on the low rate of women work participation in the formal sector.Methodology: The analytical method used in this study is a qualitative method, namely a literature review supported by take-home pay calculation simulation data on women formal sector employees regarding perceptions of tax fairness.Results: This study obtained the result that there is an unfairness in the tax regulations for working women taxpayers compared to men and this is related to the lower level of women working in the formal sector compared to men, so that the work participation rate for women is lower than for men.Conclusion: This study highlights the importance of adjusting tax policies to address gender inequality, particularly concerning the lower Non-Taxable Income (PTKP) threshold for women. The international implications of these findings call for G20 countries, including Indonesia, to incorporate gender considerations into their tax regulations, in line with OECD recommendation.Limitations: The study relies on secondary data through literature reviews and simulations, which may not fully capture real-world variables or the broader socio-economic factors that affect women's participation in the workforce.Contribution: This research is expected to contribute in the form of policy recommendations to the tax directorate general to review tax rules that accommodate tax fairness for women taxpayers. This is in line with the OECD proposal at the G20 Presidential 2022 regarding Gender-Based Taxation Policies. This is also in line with the Omnibus Law UU Number 2 of 2022 concerning Job Creation, where the Government of Indonesia has paid attention to the rights of working women and provided facilities, for example, in the form of maternity leave, menstrual leave, etc.